Five fast tales : a collection of five early readers. (New York, N.Y. : Random House, 2011)
In five stories, cars and trucks introduce simple concepts; Lightning McQueen and Mack head to a race; Lightning gets lost but makes friends; the denizens of Radiator Springs prepare for tourists; and Mater and Lightning investigate a mysterious sound.
Old, new, red, blue -- Race team -- Driving buddies -- Roadwork! -- The spooky sound.
Keywords: Automobiles -- Juvenile fiction; Vehicles -- Juvenile fiction; Automobiles, Racing -- Juvenile fiction; Friendship -- Juvenile fiction